2019
DOI: 10.1104/pp.18.01503
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of SERK3/BAK1 Regulates Plant Immunity, Development, and Cell Death

Abstract: Arabidopsis BAK1, a co-receptor of multiple receptor-like kinases undergoes proteolytic cleavage process, which is essential for its functions in plant immunity, growth and cell death control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 86 publications
0
32
1
Order By: Relevance
“…Association with different RLKs leads to different BAK1 phosphorylation code, explaining specificity of different RLKs in plant immunity and growth/development. Besides, the Ca 2+ ‐dependent proteolytic cleavage process of BAK1 is conserved in multiple plants, and the homeostasis of BAK1 mediated by a proteolytic process is also important for plant immunity, growth, and development (Zhou et al 2019). Elucidation of these codes of post‐translational modification for signaling specificity will improve our understanding of PRRs.…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…Association with different RLKs leads to different BAK1 phosphorylation code, explaining specificity of different RLKs in plant immunity and growth/development. Besides, the Ca 2+ ‐dependent proteolytic cleavage process of BAK1 is conserved in multiple plants, and the homeostasis of BAK1 mediated by a proteolytic process is also important for plant immunity, growth, and development (Zhou et al 2019). Elucidation of these codes of post‐translational modification for signaling specificity will improve our understanding of PRRs.…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…Notably, tyrosine phosphorylation is also essential for BAK1 function in immune signaling (Perraki et al , ). BAK1 is a co‐receptor for many LRR‐RKs and functions in plant immunity, growth, and development (de Oliveira et al , ; Yamada et al , ; Peng et al , ; Zhou et al , ). A recent study showed that Y403 phosphorylation is required for BAK1 function in immune signaling, highlighting the importance of tyrosine phosphorylation for this immune protein (Perraki et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro kinase activity assay was performed as previous described (Zhou et al, 2019). In brief, reactions were performed in 30 µl of kinase buffer [20 mM Tris-HCl at pH 7.5, 10 mM MgCl 2 , 5mM EGTA, 100 mM NaCl, and 1 mM dithiothreitol containing 10 µg fusion proteins with 0.1 mM cold ATP and 5 µCi ( 32 P) γ-ATP] at room temperature for 3 h with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%